(untitled) (E Global Congress, 2023)
The aim is to analyze the curing behavior of MWCNT/iPE nanocomposite in suspensions containing 1.0 wt% of COOH group modified and well-dispersed via the tip-sonication method. For this purpose, various analytical techniques, TGA analysis under non-isothermal conditions in nitrogen test revealed that the stability of nanotubes sample toward high-temperature air oxidation and assaying the impact of graphitization, during thermal decomposition in nitrogen, the MWCNT as a mass-transport protective barrier can slow down the degradation of the polymer. However, released metallic derivatives from MWCNTs interphases have significant catalytic activity on thermal degradation, which causes a reduction in the thermal stability of modified MWCNTs/iPE nanocomposites compared with the cured polyester resin. The apparent activation energies of the samples were evaluated by Kissinger and Flynne-Walle-Ozawa method. DSC results indicated that a few traces of residual solvents in the composition greatly impacted the cure reaction and subsequently affected the endothermic behaviors of the modified MWCNTs/iPE nanocomposite. The Fourier transform infrared spectroscopy (FTIR) was performed for the interpretation of the result, and the fractural conversion rates of polyester resin and nanocomposite were found to be altered depending on the solvent used.